2002
DOI: 10.1046/j.1529-8817.2002.t01-1-01100.x
|View full text |Cite
|
Sign up to set email alerts
|

DIMETHYLSULFONIOPROPIONATE CLEAVAGE BY MARINE PHYTOPLANKTON IN RESPONSE TO MECHANICAL, CHEMICAL, OR DARK STRESS1

Abstract: Several bloom‐forming marine algae produce concentrated intracellular dimethylsulfoniopropionate (DMSP) and display high DMSP cleavage activity in vitro and during lysis after grazing or viral attack. Here we show evidence for cleavage of DMSP in response to environmental cues among different strains of the haptophyte Emiliania huxleyi (Lohmann) Hay et Mohler and the dinoflagellate Alexandrium spp. (Halim). Sparging or shaking live cells of either taxon increased dimethyl sulfide (DMS), especially in dinoflage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
83
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(86 citation statements)
references
References 51 publications
3
83
0
Order By: Relevance
“…Overall, maximum DMSP t and DMS values associated to the Phaeocystis bloom in this near-shore shallow and very productive coastal environment (1740 and 250 nmol L − 1 , respectively) were one to two orders of magnitude higher than those typically encountered in open oceanic waters, as well as those in the deeper stratified northern North Sea even during blooms of high DMSP producing coccolithophorids. Wolfe et al, 2002 …”
Section: Discussionmentioning
confidence: 99%
“…Overall, maximum DMSP t and DMS values associated to the Phaeocystis bloom in this near-shore shallow and very productive coastal environment (1740 and 250 nmol L − 1 , respectively) were one to two orders of magnitude higher than those typically encountered in open oceanic waters, as well as those in the deeper stratified northern North Sea even during blooms of high DMSP producing coccolithophorids. Wolfe et al, 2002 …”
Section: Discussionmentioning
confidence: 99%
“…Hence, we might have underestimated A, and as a consequence also B, when conversion or exudation of DMSP took place during the growth phase. We have reason to believe that this is a minor part of the particulate fraction (van Rijssel and Gieskes 2002;Wolfe et al 2002), but even when it is substantial, this would not have affected the results substantially: A doubling of A, and hence an almost doubling of B, would have resulted in a lower calculated 64 MP eq by only 1% and hence an increase of the equilibrium fractionation factors (α EQ ) by 2%.…”
mentioning
confidence: 99%
“…DMSP and its cleavage products generated via the action of DL have been suggested to have many functions within the cell relating to metabolic processes and maintaining homeostasis (for more details see Stefels 2000; Simo 2001), for example as an antioxidant cascade (Sunda et al 2002). DMSP and its downstream products have also been implicated in cellular defense against grazing (Wolfe et al 1997) and viral infection (Evans et al 2006b). …”
mentioning
confidence: 99%
“…Autolysis (Nguyen et al 1988), grazing (Dacey and Wakeham 1986), viral lysis , and mechanical and chemical stress (Wolfe et al 2002) have all been shown to increase DMS production. During grazing by Oxyrrhis marina on Emiliania huxleyi it was established that the concentration of DMS generated was directly related to the activity of the DL of the prey organism (Wolfe and Steinke 1996). Previously DMS production during viral lysis of phytoplankton has only been shown in the presence of bacteria (Hill et al 1998).…”
mentioning
confidence: 99%